Psychological Analysis of Landscape Linguistics in Public Spaces in Buru Island - Yulismayanti Yulismayanti; Risman Iye; Susiati Susiati; Harziko Harziko; Taufik Taufik; Fithriyah Inda Nur Abida (Hasanuddin University, 2022)
Landscape Linguistics is a study that focuses on the use of language in public spaces, both monolingual, bilingual and multilingual. The purpose of this study is to analyze the linguistic psychology of landscapes in public spaces on Buru Island. The research method used is qualitative. In this study, researchers took sources from the nameplate or baleho found on Buru Island, precisely in Namlea Village. The data sources are several photos in public places on Buru Island. Analysis of research data, namely when researchers collect the results of information board documentation scattered on Buru Island, all of the documentation is classified according to their respective characteristics, namely, signboards, billboards and other information. Then the meaning and function are determined by using Landscape linguistic studies. The results of the study found that in the public space of the Buru Island community there were two variations of the language used, namely Indonesian and the Maluku dialect, as well as the Landscape function, namely Formal and Informal